Batch-related sterile endophthalmitis following intravitreal injection of bevacizumab - Entezari, Morteza (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: To report a series of patients with sterile endophthalmitis after intravitreal bevacizumab (IVB) injection from 2 different batches of bevacizumab. MATERIALS AND METHODS: Records of 11 eyes with severe inflammation after IVB injections from two different batches (7 eyes from one and 4 from the other) on two separate days were evaluated. Fifteen eyes of 15 patients in one day were treated with one batch and 18 eyes of 17 patients were treated another day using another batch injected for different retinal diseases. Each batch was opened on the day of injection. We used commercially available bevacizumab (100 mg/4 ml) kept at 4°C. Severe cases with hypopyon were admitted to the ward and underwent anterior chamber and vitreous tap for direct smear and culture. RESULTS: Pain, redness and decreased vision began after 11-17 days. All had anterior chamber and vitreous reactions and 5 had hypopyon. Antibiotics and corticosteroids were initiated immediately, but the antibiotics were discontinued after negative culture results. Visual acuity returned to pre-injection levels in 10 eyes after 1 month and only in one eye pars plana vitrectomy was performed. Mean VA at the time of presentation with inflammation (1.76 ± 0.78 logMAR) decreased significantly (P =0.008) compared to the initial mean corrected VA (1.18 ± 0.55 logMAR); however, final mean corrected VA (1.02 ± 0.48 logMAR) improved in comparison with the baseline but not to a significant level (P =0.159). CONCLUSIONS: We report a cluster of sterile endophthalmitis following intravitreal injection of bevacizumab from the same batch of bevacizumab that has a favorable prognosis.